Well-Posedness of a Parabolic Equation with Involution. (3rd October 2017) - Ashyralyev, Allaberen; Sarsenbi, Abdizhahan
ABSTRACT: In the present study, the problem of a parabolic equation with involution is investigated. The stability and coercive stability estimates in Hölder norms for the solution of this problem are established.